2019
DOI: 10.2147/idr.s234211
|View full text |Cite
|
Sign up to set email alerts
|

<p>Colistin Plus Carbapenem versus Colistin Monotherapy in the Treatment of Carbapenem-Resistant <em>Acinetobacter baumannii</em> Pneumonia</p>

Abstract: Purpose: Colistin alone may not be sufficient for treating carbapenem-resistant Acinetobacter baumannii (CRAB); thus, efforts are needed to increase treatment success rates. We compared the effects of colistin plus carbapenem therapy versus colistin monotherapy in treating pneumonia caused by CRAB and attempted to identify specific populations or factors that could benefit from combination therapy. Methods: We retrospectively collected data on cases of CRAB pneumonia. The patients were divided into colistin pl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

6
19
1
2

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 29 publications
(28 citation statements)
references
References 20 publications
6
19
1
2
Order By: Relevance
“…Our findings showed that the maximal clinical benefit of combination therapy was observed in our patients with critical illness, which is consistent with data from a previous study [ 15 , 16 ]. A retrospective study comparing colistin monotherapy with colistin plus a carbapenem combination therapy on 160 cases of CRAB pneumonia showed no significant difference in 14-day mortality between the combination and monotherapy groups (24.1% vs. 20.8%, p = 0.616).…”
Section: Discussionsupporting
confidence: 93%
See 1 more Smart Citation
“…Our findings showed that the maximal clinical benefit of combination therapy was observed in our patients with critical illness, which is consistent with data from a previous study [ 15 , 16 ]. A retrospective study comparing colistin monotherapy with colistin plus a carbapenem combination therapy on 160 cases of CRAB pneumonia showed no significant difference in 14-day mortality between the combination and monotherapy groups (24.1% vs. 20.8%, p = 0.616).…”
Section: Discussionsupporting
confidence: 93%
“…A retrospective study comparing colistin monotherapy with colistin plus a carbapenem combination therapy on 160 cases of CRAB pneumonia showed no significant difference in 14-day mortality between the combination and monotherapy groups (24.1% vs. 20.8%, p = 0.616). However, after adjusting for disease severity according to APACHE II score, the 14-day mortality was significantly lower in the combination group compared to the monotherapy group among patients with APACHE II scores of 25–29 points (9.1% vs. 53.8%, p = 0.020) [ 15 ]. In a previous retrospective study that evaluated data from 71 patients with CRAB bacteraemia treated with colistin monotherapy and colistin plus meropenem combination therapy, mortality tended to be higher in the monotherapy group, but the difference was not statistically significant (47.5% vs. 25.8%).…”
Section: Discussionmentioning
confidence: 99%
“…Other combination regimens suggest increased efficacy of sulbactam with cefepime, meropenem, imipenem, amikacin, or rifampin [123]. Alternative combinations include colistin-tigecycline and colistin-carbapenem therapy, with the latter perhaps the most supported [36], and have been recommended in several trials [124][125][126]. Furthermore, a recent investigation has highlighted a remarkable synergistic interaction between colistin and vancomycin [127].…”
Section: Mechanisms Of Antibiotic Resistance In a Baumanniimentioning
confidence: 99%
“…Data from some in-vitro studies have shown synergistic effects of colistin and meropenem combination therapy (Tängdén et al, 2017). On the other hand, another previous study reported no significant difference in antibacterial effect between colistin monotherapy and colistin plus meropenem combination (Shi et al, 2019). In addition, clinical data are very limited and have controversial results.…”
Section: Introductionmentioning
confidence: 99%